Association of lifetime blood pressure with adulthood exercise blood pressure response: the cardiovascular risk in young Finns study - Kähönen Emilia; Aatola Heikki; Pälve Kristiina; Hulkkonen Janne; Haarala Atte; Sipilä Kalle; Juonala Markus; Lehtimäki Terho; Raitakari Olli T; Kähönen Mika; Hutri-Kähönen Nina (TAYLOR & FRANCIS LTD, 2025)
Purpose
Elevated blood pressure (BP) in childhood has been associated with increased adulthood BP. However, BP and its change from childhood to adulthood and the risk of exaggerated adulthood exercise BP response are largely unknown. Therefore, we studied the association of childhood and adulthood BP with adulthood exercise BP response.
Materials and methods
This investigation consisted of 406 individuals participating in the ongoing Cardiovascular Risk in Young Finns Study (baseline in 1980, at age of 6-18 years; follow-up in adulthood in 27-29 years since baseline). In childhood BP was classified as elevated according to the tables from the International Child Blood Pressure References Establishment Consortium, while in adulthood BP was considered elevated if systolic BP was >= 120 mmHg or diastolic BP was >= 80 mmHg or if use of antihypertensive medications was self-reported. A maximal cardiopulmonary exercise test with BP measurements was performed by participants in 2008-2009, and exercise BP was considered exaggerated (EEBP) if peak systolic blood pressure exceeded 210 mmHg in men and 190 mmHg in women.
Results
Participants with consistently high BP from childhood to adulthood and individuals with normal childhood but high adulthood BP had an increased risk of EEBP response in adulthood (relative risk [95% confidence interval], 3.32 [2.05-5.40] and 3.03 [1.77-5.17], respectively) in comparison with individuals with normal BP both in childhood and adulthood. Interestingly, individuals with elevated BP in childhood but not in adulthood also had an increased risk of EEBP [relative risk [95% confidence interval], 2.17 [1.35-3.50]).
Conclusions
These findings reinforce the importance of achieving and sustaining normal blood pressure from childhood through adulthood.